Increase of Plasminogen Activator Inhibitor Levels Predicts Outcome of Leukocytopenic Patients with Sepsis - Mesters, R M; Flörke, N; Ostermann, H; Kienast, J (Thrombosis and Haemostasis, 1996)
Variables of the fibrinolytic system were prospectively studied in patients with haematologic malignancies in chemotherapy-induced leukocytopenia at onset and during the course of septicemia to evaluate their prognostic value. This group of patients was chosen because of their high risk of developing severe septic complications, thus allowing serial prospective testing of fibrinolytic variables prior to and during evolving sepsis or septic shock. 62 patients with febrile infectious events were accrued to the study. Of these, 13 patients progressed to severe sepsis and an additional 13 patients to septic shock as defined according to standard diagnostic criteria. At onset of fever, plasminogen activator inhibitor (PAI) activity and PAI-1 antigen levels increased from normal baseline levels and were significantly higher in the group of patients who developed septic shock compared to those with severe sepsis (medians: 10.6 versus 1.3 U/ml, p = 0.0001; 50.0 versus 5.0 ng/ml, p = 0.0002). The increase in PAI activity and antigen in septic shock was accompanied by an increase in tissue-type plasminogen activator antigen and total fibrin(ogen) degradation products and a decrease in alpha2-antiplasmin activity (p < 0.006). In contrast, in the group of patients that developed severe sepsis the variables of the fibrinolytic system remained unchanged at onset of fever. These differences between septic shock apd severe sepsis were sustained throughout the septic episode for all variables (p <0.0001). PAI activity of >5 U/ml at onset of fever predicted a lethal outcome with a sensitivity of 92% and a specificity of 100%. Thus, septic shock in leukocytopenia is associated with significant activation of the fibrinolytic system presumably as a response of the vascular endothelium to inflammatory injury. Furthermore, PAI activity measurements are sensitive markers of an unfavourable prognosis.